2022
DOI: 10.26803/ijlter.21.9.24
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Digital Learning in Enhancing Educational Values: Online Socialization and Its Effect on Peer Learning, Collaborative Skills and Knowledge Construction

Abstract: This study aimed to examine the advantages of online socializing and digital learning for the growth of interpersonal, peer learning and collaborative skills. The impact of these three skills on knowledge construction was evaluated. The Salmon five step e-moderation model has been used to explore the many phases of learning in a digital environment. This study examined the first stage of the e-moderation model, which is the respondents' internet accessibility, and the stage of knowledge construction in digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…AI ChatGPT is used from elementary school to college. In higher education, the application of ChatGPT is a form of digital transformation that requires much preparation, skills, digital literacy (Akour & Alenezi, 2022), adequate academic performance, social-media networking (Sobaih et al, 2022), social-network systems (Yusof et al, 2022), text drafting, data processing, and curriculum development (Renato et al, 2023). In the world of education and research, ChatGPT is used as a tool to organize writing, answer cross-cutting questions (Alnaqbi & Fouda, 2023), to answer complex topics, in language training, virtual tutoring, programming exercises, and to assist in the research process (Rahman & Watanobe, 2023), assist with writing, research, academic publications (Halaweh, 2023), and manuscript editing (Cooper, 2023).…”
Section: Use Of Ai Chatgpt In Educationmentioning
confidence: 99%
“…AI ChatGPT is used from elementary school to college. In higher education, the application of ChatGPT is a form of digital transformation that requires much preparation, skills, digital literacy (Akour & Alenezi, 2022), adequate academic performance, social-media networking (Sobaih et al, 2022), social-network systems (Yusof et al, 2022), text drafting, data processing, and curriculum development (Renato et al, 2023). In the world of education and research, ChatGPT is used as a tool to organize writing, answer cross-cutting questions (Alnaqbi & Fouda, 2023), to answer complex topics, in language training, virtual tutoring, programming exercises, and to assist in the research process (Rahman & Watanobe, 2023), assist with writing, research, academic publications (Halaweh, 2023), and manuscript editing (Cooper, 2023).…”
Section: Use Of Ai Chatgpt In Educationmentioning
confidence: 99%
“…Several research have been undertaken on the topic of collaborative skills. Yusof et al (2022) found that online learning involves a significant amount of interpersonal, peer learning, and collaborative activities that contribute to knowledge generation. The three abilities of peer learning, collaborative skills, and knowledge construction are positively correlated as indicators of educational values.…”
Section: Introductionmentioning
confidence: 99%